Women Empowerment in Different Household Issues of Bangladesh - Zaman, Umme Rumana; Rahman, Md Mizanur; Hussain, Syed Md Akram; Zaki, Mahbub (Bangladesh Medical Journal, 2009)
During the last few decades, developing countries in the world has been going through an intensive transformation process related to change in demographic and in the use of human capital. These changes have important implications for women empowerment which they tend to systematically alter the marginal utility of consumption over the life cycle. Considering this view, this cross sectional study was aimed to find out the level of women empowerment in purposively selected areas of Bangladesh. A total 206 married women were interviewed face to face using structured questionnaire. To assess the level of women empowerment, a series of questions were asked with a view to assessing the level of participation in different household and family matters. On the basis of 18 variables, a composite level of women empowerment was assessed by Principal Component Analysis (PCA) using computer simulation and categorized into three groups. It was found that 40% had poor level of empowerment, 19% had fair and 41 had good level of women empowerment. Bi-variate analysis revealed that level of women empowerment was found to be high among the respondents living in urban areas, less number of children, religion Islam, higher level of education of husband and wife, working status of husband and wife, monthly family income and living in pucca house condition (p<0.05). However, no statistically significant association was found between current age of husband and wife, age at marriage and spousal age difference (p>0.05). Though the study had some limitations, but the study finding would be helpful for policymakers concerning implementing the programme for empowering women through different intervention programmes. Key words: Women Empowerment, Household Decision Making, Bangladesh DOI: 10.3329/bmj.v37i2.3591 Bangladesh Medical Journal 37(2) 2008 41-45